2015
DOI: 10.1248/bpb.b14-00721
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Studies of Levothyroxine Sodium Hydrate Suppository Provided as a Hospital Preparation

Abstract: The levothyroxine sodium hydrate suppository (L-T 4 -suppository) is provided as a hospital preparation for the treatment of hypothyroid patients with dysphagia in Japan because only oral preparations of levothyroxine sodium (L-T 4 ) are approved for the treatment of hypothyroidism. However, it has been found that serum thyroxine and triiodothyronine levels do not increase as expected with the hospital preparation, requiring a higher dosage of L-T 4 in the L-T 4 -suppository than in the oral preparations. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A study evaluating the efficacy and pharmacokinetics of LT4 in human subjects with hypothyroidism demonstrated that LT4 suppositories had lower bioavailability and efficacy compared to oral LT4, even though T4 levels can be maintained in patients with hypothyroidism by administering LT4 suppositories at approximately twice the oral dose [ 5 ]. The lower bioavailability of rectal LT4 compared to its oral counterpart has been attributed to the low level of release LT4 in the rectum [ 6 ]. The rectal route seemed appealing, but LT4 suppositories were also not available.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the efficacy and pharmacokinetics of LT4 in human subjects with hypothyroidism demonstrated that LT4 suppositories had lower bioavailability and efficacy compared to oral LT4, even though T4 levels can be maintained in patients with hypothyroidism by administering LT4 suppositories at approximately twice the oral dose [ 5 ]. The lower bioavailability of rectal LT4 compared to its oral counterpart has been attributed to the low level of release LT4 in the rectum [ 6 ]. The rectal route seemed appealing, but LT4 suppositories were also not available.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, rectal pH impairs the absorption of LT4. Hamada et al demonstrated that although LT4 suppository content was uniform and stable over 90 days, its release rate correlated directly with rectal pH ( 259 ). A 240-minute in vitro experiment showed an ∼20% release at pH 8.2 and undetectable release at pH <7.2.…”
Section: Novel Drug Delivery Formulationsmentioning
confidence: 99%
“…Several recent publications investigated the stability of levothyroxine, and the development of new formulations with better stability [6,[8][9][10][11][12][13][14][15][16][17][18][19]. The effect of excipients on the stability of levothyroxine sodium pentahydrate tablets was studied by Gupta et al and reported in 1990 [20] and aimed towards the transformations that took place in a solid formulation containing LTSS along with excipients that act as a catalyst to decomposition of API, leading to a shorter shelf-life of the product than the one mentioned by the manufacturer.…”
Section: Introductionmentioning
confidence: 99%